The Activity of Ni-Based Catalysts on Steam Reforming of Glycerol for Hydrogen Production - EBSHISH, ALI SALEM; Yaakob, Zahira; Narayanan, Binitha; Bshish, Ahmed M.; Wan Daud, Wan Ramli (International Journal of Integrated Engineering, 2011)
Glycerol, the readily available bio renewable material, is effectively utilized for hydrogen production by a steam reforming reaction. The experiments were carried out in a continuous flow fixed-bed reactor over Nickel supported alumina catalysts under atmospheric pressure at 600°C and three hours reaction time. 5%wt Ni was loaded over γ-Al2O3 and effect of promoter metals such as Fe and Co over Ni/γ-Al2O3 catalytic systems were evaluated. The catalysts were characterized by BET surface area, XRD and SEM techniques. The activity results showed that the addition of Co enhanced the catalyst performance. The catalysts exhibited a good activity and selectivity to hydrogen.